Evolution of postzygotic reproductive isolation in galliform birds: analysis of first and second hybrid generations and backcrosses - Arrieta, Ramiro Santiago (2013)
The process of speciation is a crucial aspect of evolutionary biology. In this study, we analysed the patterns of evolution of postzygotic reproductive isolation in Galliformes using information on hybridization and genetic distance among species. Four main patterns arose: (1) hybrid inviability and sterility in F1 hybrids increase as species diverge; (2) the presence of geographical overlap does not affect the evolution of postzygotic isolation; (3) the galliforms follow Haldane’s rule; (4) hybrid inviability is higher in F2 than in F1 hybrids, but does not appear to be increased in the backcrosses. This study contributes to the growing evidence suggesting that the patterns of evolution of postzygotic isolation and the process of speciation are shared among avian groups (and animals in general). In particular, our results support the notion of F2 hybrid inviability as being key for the maintenance of species genetic integrity when prezygotic isolation barriers are overcome in closely related species, in which postzygotic isolation in the F1 hybrid might still not be fully developed. To the contrary, hybrids from backcrosses did not show serious inviability problems (at least not more than F1 hybrids), demonstrating that they could generate gene flow among bird species.